A deeper inquiry into the association between lucid dreams and video game play - Gackenbach, Jayne; Hunt, Harry T. (My University, 2014)
After summarizing the previous research on the association between video game play, meditative absorption, and dream lucidity, three types of considerations of lucidity and gaming were explored in this chapter: the association of lucidity in gamers with metacognition, dream bizarreness, and nonlucid dream content. In terms of specific forms of metacognition in dreams, it appears that gaming adds a dimension to the lucid dreams of gamers such that their full potential for focused problem solving is expressed, very much like with the strategies of video gaming. Some research indicated gamers’ dream included an enhanced bizarreness, but lucidity was not found to mitigate that relationship. Finally, comparing the lucid and nonlucid dreams of gamers, it was concluded that lucidity in gamers’ dreams emphasized the already generally positive dream experience of being lucid in sleep, including enhanced aggression that facilitated the sense of empowerment (also typical of video game playing). Not only is there some indication of more lucidity in gamers’ dreams, but that lucidity seems to be further enhanced by the gaming experience.
Keywords: Computer Games; Dream Content; Lucid Dreaming; Metacognition